Effect of mindfulness on online impulse buying: Moderated mediation model of problematic internet use and emotional intelligence - Vihari, Nitin Simha; Sinha, Nishit Kumar; Tyagi, Akansha; Mittal, Saurabh (Frontiers in Psychology, 2022)
Introduction Online impulse buying behavior is an unplanned urge to buy a product or service in an online setting and it has several negative consequences for customers, such as guilt and financial distress, and e-commerce firms, such as higher returns and customer complaints. Evidently, it is important to examine the various psychological processes which may assist in a better understanding, therefore addressing the high prevalence of online impulse buying. This study builds upon self-regulation theory to explore how mindfulness influences online impulse buying, and examines problematic internet use as a mediator in the relationship between mindfulness and online impulse buying. Further, this study investigates how emotional intelligence as a moderator plays the role of a suppressant on the adverse impact of problematic Internet use which fuels online impulse buying. Method A total of 598 individuals working with various servicebased industries responded to the questionnaire. Multiple regression and moderated mediation analysis was used using SPSS and AMOS for analyzing the data. Result Problematic internet use mediates the relationship between mindfulness and online impulse buying behavior. Emotional intelligence negatively moderates the relationship between problematic internet use and online impulse buying behavior. Discussion This study findings outlined the inverse relationship of mindfulness & online impulse buying, along with the mediating effect of problematic internet use between mindfulness and online impulse buying. Further, this study showed how emotional intelligence played an important role as a moderator by suppressing the adverse impact of problematic Internet use and preventing online impulse buying. The study offers implications to online marketers in regulating the unplanned purchase process—while minimizing uninhibited buying behavior that leads to regret, and the subsequent intention to return products. Further, social and theoretical implications are discussed.